ACQUISITION OF SENTENCES BY A THREE-YEAR-OLD INDONESIAN BOY: A CASE STUDY ON M. GENTAMAS RANSI ALDEN - Fadhila . Hayani; Siti Aisyah Ginting; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
This study was investigated about the acquisition of sentences by three-year-old Indonesian boy, M. Gentamas Ransi Alden. The objective of this study were to investigated the sentences that produced by three years old Indonesia boy, and to explain the reason for the sentences produced based on mood in a case study on M. Gentamas Ransi Alden. This research was conducted by using descriptive qualitative research design. The data were utterances from a three years old Indonesia boy and source of data taken from M. Gentamas Ransi Alden. For the duration of almost three months, the researcher observed and recorded the subject’s produced sounds, words, and sentences. The researcher also observed how the learner interacts with various linguistics inputs to see how the subject processes them. Finally, the researcher also observed him as interacts with people to determine the levels of the various constructs of his communicative competence. The result of the data showed that the subject already acquired the sentences based on mood, they are: 1) declarative sentences, 2) imperative sentences, 3) exclamatory sentences, and 4) interrogative sentences. In acquiring the second language, the research subject acquired the sentence during the process of imitating from their parents since they start over to speak. The subject used a declarative sentence to declare their statements, the interrogative sentence they use it to ask about information of something, the exclamatory sentences they use to shows about the emotion and also to declare their statement, and the imperative sentences to ask another to do something. Keywords: Children Sentence Acquisition, Kinds of Sentences, a Three Year Old, Indonesian Boy